Investigation Of Ni-Cu As Ohmic Contact On P-Type Gan_ Investigation Of Ni-Cu As Ohmic Contact On P-Type Gan_Investigation Of Ni-Cu As Ohmic Contact On P-Type Gan - Koe, Mei Yen (Universiti Sains Malaysia, 2017)
Nowadays, wide band gap semiconductors like Gallium Nitride (GaN) are considered the most promising materials for the next generation of power electronic devices. The properties of GaN like wide band gap, high critical electric field and high thermal conductivity give the possibility to fabricate devices operating at much higher voltages, temperatures and frequencies than in Silicon. Devices based on wide band gap materials enable a significant reduction of the power losses and an increase of the energy efficiency. In this project aims to study the effect of different composition and combination of Ni/Cu on the Ohmic contact between metal and p-GaN, the effect of different annealing temperature on the Ohmic contact between metal and p-GaN and to investigate the specific contact resistivity at the interface between the metal and the semiconductor through Circular transmission line model (CTLM) via varying the inner radius and gap. The pattern were produced using photolithography process. Copper (Cu) and nickel (Ni) were deposited using thermal evaporation method. Ni were deposited first, followed by Cu on the Mg-doped P-type GaN (0001) on Sapphire. The thickness of metal deposited were controlled by manipulating the deposition time in the range of 15 s to 60 s. The annealing temperature 550°C, 600°C, 650°C and 700°C were applied to each of the composition. AFM were used to determine the surface morphology of the sample. XRD were used to identify the phase present in the sample. Electrical characterization were obtained using SPA machine and specific contact resistance of the Ohmic contact can be determined. When reverse voltage 0 v to -2 V and forward voltage 0 v to 2 V supplied, the sample with lowest specific contact resistance, ρc 8.399 x 1011 Ωcm2 and 7.299 x 1012 Ωcm2 respectively is Ni/Cu (150 nm/150 nm) annealed at 550°C. The surface roughness Ra and RMS are 64.63 nm and 86.35 nm respectively which investigate using AFM. From XRD result, the phase present for this sample are CuO (110), CuO (111̅) and GaN (222). From FESEM, the thickness of metal obtained for this sample were about 300 nm and EDX were used to identify the element on the sample.